Strengthening The Motivation Of Community Health Center Officers In Increasing Community Satisfaction Through The Integration Of The Job Demands–Resources Model And Conservation Of Resources - Sentot Imam Suprapto; Linda Kristian Ningtiyas (CV. AFDIFAL MAJU BERKAH, 2026)
Digital transformation in primary health care services has increased work demands among health workers, particularly in administrative tasks and application-based reporting systems. This condition may affect the work motivation of Puskesmas staff if it is not balanced with adequate work resources. This community service activity aimed to strengthen the work motivation of Puskesmas health workers through an integrative approach of the Job Demands–Resources (JD-R) model and the Conservation of Resources (COR) theory. The activity was conducted at UPTD Muara Rapak Public Health Center, Balikpapan, using a descriptive participatory approach. The stages included identification of work-related problems, prioritization of key issues, implementation of educational and reflective interventions, and initial evaluation of staff responses. The intervention focused on improving staff understanding of the balance between job demands and job resources, as well as the importance of protecting individual resources in dealing with digital work demands. The results indicated an improvement in staff awareness and understanding regarding workload management, utilization of organizational support, and maintenance of individual resources. The integration of the JD-R model and COR theory is considered relevant as a conceptual basis for strengthening health workers’ motivation in primary health care settings. This activity is expected to serve as an initial reference for developing human resource strengthening strategies in primary health care services.